Atomic absorption spectrometry determination of Cd, Cu, Fe, Ni, Pb, Zn, and Tl traces in seawater following flotation separation - Kojuncu, Y; Bundalevska, JM; Ay, Ü; Cundeva, K; Stafilov, T; Akçin, G (TAYLOR & FRANCIS INC, 2004)
A fast method for separation of Cd, Cu, Fe, Ni, Pb, Zn, and Tl from seawater before their determination by atomic absorption spectrometry (AAS) is described. The ability of Co(III) hexamethylenedithiocarbamate, Co(HMDTC)(3), as a flotation collector for metals from seawater was investigated. The influence of pH of the media, as one of the crucial parameters for effective flotation, as well as mass of cobalt as one of the constituents of a chelatometric collector was optimized. The used mode of atomization flame (FAAS) or electrothermal (ETAAS) depends on the concentration level of analyte present in the seawater sample investigated. The AAS method following flotation was compared with the method of inductively coupled plasma-atomic emission spectrometry (ICP-AES). The limit of detection (LOD) of each analyte obtained by FAAS or ETAAS is determined: flotation/ETAAS for Cd is 0.010 mug/L, for Cu 0.034 mug/L, for Ni 0.305 mug/L, for Pb 0.290 mug/L, and for Tl 0.032 mug/L, whereas flotation/FAAS for Fe is 0.890 mug/L and for Zn 0.994 mg/L.
Keywords: heavy metals; seawater; determination; matrix interferences; flotation; cobalt(III) hexamethylenedithiocarbamate; AAS; ICP-AES; PRECONCENTRATION; HEXAMETHYLENEDITHIOCARBAMATE; CADMIUM; NICKEL; WATER; Chemistry; Engineering